Communication as a Mediator for the Effect of Job Insecurity on Nurse Performance in Level III Hospital 04.06.03 Dr. Soetarto Yogyakarta - Winda Novitasari; Purbudi Wahyuni; Khoirul Hikmah (Journal of Business Innovation and Research, 2023)
The purpose of this study was to analyze the performance of nurses at Level III Hospital 04.06.03 Dr. Soetarto by using job insecurity variables and communication mediation in this relationship. The population of this study were all nurses at Level III Hospital 04.06.03 Dr. Soetarto totaling 111. The sampling method is based on non-probability sampling technique using saturated sampling. The data collection technique used a questionnaire tool and was measured using a Likert rating scale. The analytical tool used is the Smart PLS software. The results show that there is a significant negative effect between job insecurity on performance, there is a significant positive effect between communication on performance, and it is known that communication can mediate the effect of job insecurity on performance. So it can be concluded that H1, H2, and H3 are accepted. The results of this study support the research of Chirumbolo and Areni (2005); Adesubomi (2018); Femi (2014); and Kibe (2014) and do not support the research of Shin and Hur (2019).